GE_GERICHTE P/11124/2018 vom 15. Mai 2022 - GE Cour de justice (2022)
IN DUBIO PRO REO;LÉSION CORPORELLE SIMPLE;MENACE(DROIT PÉNAL);VIOLENCE DOMESTIQUE | CP.123.ch1; CP.123.al3.ch2; CP.180.al1; CP.180.al2.leta; CPP.406.al2